The Impossible Trinity of Denial. European Economic Governance in a Conceptual Framework - István BENCZES (Transylvanian Review of Administrative Sciences, 2013)
The first ten years of the Economic and Monetary Union were a remarkable success story. Nevertheless, the European financial-cum-sovereign- debt-crisis made it clear that the original design of European economic governance is not feasible any longer. The crisis compelled Europeans to admit that the implicit consent of Maastricht on a triple denial with regard to the single currency area, i.e., (1) no exit, (2) no bail-out, and (3) no default, is no longer tenable. By introducing the concept of the ‘impossible trinity of denial’, the current paper argues that pursuing these three goals simultaneously is not attainable, and that one of these should be sacrificed in order for the single currency to survive the current crisis. Also, supranational institutions should enjoy more control over crisis resolution in the future.